SAHA and/or MG132 reverse the aggressive phenotypes of glioma cells: An in vitro and vivo study - Yang, Xue-feng (Oncotarget, 2016)
To elucidate the anti-tumor effects and molecular mechanisms of SAHA (a histone deacetylase inhibitor) and MG132 (a proteasome inhibitor) on the aggressive phenotypes of glioma cells, we treated U87 and U251 cells with SAHA or/and MG132, and detected phenotypes’ assays with phenotype-related molecules examined. It was found that SAHA or/and MG132 treatment suppressed proliferation in both concentration- and time-dependent manners, inhibited energy metabolism, migration, invasion and lamellipodia formation, and induced G(2) arrest and apoptosis in the glioma cells. The treatment with SAHA increased the expression of acetyl-histones 3 and 4, which were recruited to the promoters of p21, p27, Cyclin D1, c-myc and Nanog to down-regulate their transcriptional levels. Expression of acetyl-histones 3 and 4 was higher in gliomas than normal brain tissues. Both drugs’ exposure suppressed tumor growth in nude mice by inducing apoptosis and inhibiting proliferation, but increased serum aminotransferase and creatinine. These results indicated that SAHA and/or MG132 may suppress the aggressive phenotypes of glioma cells. They might be employed to treat the glioma if both hepatic and renal injuries are prevented.